An updated checklist of the millipedes of Vietnam and research perspectives (Arthropoda, Diplopoda) - Nguyen, Anh D.; Nguyen, Thu Anh T.; Le, Anh H.; Le, Son X.; Tran, Binh T.t. (Zootaxa, 2025)
The checklist of the millipedes of Vietnam was re-documented and updated after 20 years. A total of 280 species belonging to 97 genera, 31 families and 14 orders have been recorded. Of these, 246 species and 21 genera are considered to be endemic to the Vietnam fauna. Four previously listed species, Unixenus sp.; Platyrhacus marginellis Silvestri, 1911; Platyrhacus bouvieri Brölemann, 1896; and Oxidus gracilis (C.L. Koch, 1847) are removed from the current list. Sundanina cochinchina Nguyen, 2010 is transferred to the genus Enghoffosoma Golovatch, 1993 as Enghoffosoma cochinchina (Nguyen, 2010) comb. nov. Nesorthomorpha montana Nguyen, Tran & Le, 2018 is synonymized with Antheromorpha nguyeni Likhitrakarn, Golovatch, Semenyuk & Panha, 2019 syn. nov..